2018
DOI: 10.1002/2017gl076662
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Maintenance of Slowly Varying Equatorial Currents by Intraseasonal Variability

Abstract: Recent evidence from mooring data in the equatorial Atlantic reveals that semiannual and longer time scale ocean current variability is close to being resonant with equatorial basin modes. Here we show that intraseasonal variability, with time scales of tens of days, provides the energy to maintain these resonant basin modes against dissipation. The mechanism is analogous to that by which storm systems in the atmosphere act to maintain the atmospheric jet stream. We demonstrate the mechanism using an idealized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 33 publications
9
34
0
Order By: Relevance
“…Rossby waves, instead of nonlinear eddies, have been shown to play a significant role in the formation of mean jet-like currents in some studies (see [109] and references therein). Rossby waves can be important to explain other jet-like structures observed in the present simulation, in particular, the western region or deeper low latitude intermediate currents [23,44,45,124].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Rossby waves, instead of nonlinear eddies, have been shown to play a significant role in the formation of mean jet-like currents in some studies (see [109] and references therein). Rossby waves can be important to explain other jet-like structures observed in the present simulation, in particular, the western region or deeper low latitude intermediate currents [23,44,45,124].…”
Section: Discussionmentioning
confidence: 72%
“…Huttl-Kabus et al [21] showed that the cores of NEUC and SEUC mostly originate from the southeastern tropical Atlantic. Jochum and Malanotte-Rizzoli [22] used idealized simulations to show that tropical instability waves (TIW) helped to maintain the SEUC against dissipation west of 10 • W. Greatbatch et al [23] showed that intraseasonal variability ( 10 s of days) provides the energy to maintain semiannual and longer time scale ocean currents against dissipation, but they focused on the Equatorial Deep Jets (EDJ). In the Gulf of Guinea, there is also a strong seasonal cycle associated with the annual equatorial upwelling forced by the trade winds and the formation of the so called cold-tongue from June to August and a second shorter season from November to December.…”
Section: Introductionmentioning
confidence: 99%
“…Idealized simulations (Ascani et al, ) and the reconstruction of EDJ forcing derived from the 23°W mooring data (Claus et al, ) suggest an energy transfer from downward‐propagating intraseasonal Yanai waves to the EDJ at intermediate depths. Using idealized simulations and velocity data from three moorings along 23°W between 0.75°N and 0.75°S, Greatbatch et al () showed that the meridional flux of zonal momentum associated with intraseasonal variability acts to maintain the EDJ against dissipation. The inclusion of EDJ or their effects in coupled climate simulations remains an open issue to be solved in the future.…”
Section: Additional Results In Cooperation With Other National and Inmentioning
confidence: 99%
“…Using idealized simulations and velocity data from three moorings along 23°W between 0.75°N and 0.75°S, Greatbatch et al (2018) showed that the meridional flux of zonal momentum associated with intraseasonal variability acts to maintain the EDJ against dissipation. The inclusion of EDJ or their effects in coupled climate simulations remains an open issue to be solved in the future.…”
Section: Edj and Possible Climate Impactsmentioning
confidence: 99%
See 1 more Smart Citation